Effectiveness of preoperative education on anxiety reduction among surgical patients in Indonesian hospitals: A randomized controlled trial - Siti Utami Dewi; Hamudi Prasestiyo (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Preoperative anxiety is a common and clinically significant issue among surgical patients, contributing to adverse perioperative outcomes. Despite growing attention to patient-centered care, structured educational interventions remain inconsistently implemented in Indonesian hospitals. This study aimed to evaluate the effectiveness of structured preoperative education in reducing anxiety among surgical patients. Research Methodology: A parallel-group randomized controlled trial was conducted in two tertiary hospitals in Indonesia from January to April 2026. A total of 140 adult patients scheduled for elective surgery were randomly assigned to an intervention group (n = 70) that received structured preoperative education or a control group (n = 70) that received standard care. Anxiety was measured using the State-Trait Anxiety Inventory (STAI). Data were analyzed using independent t-tests and multiple linear regression, with α = 0.05. Results: Baseline characteristics were comparable between groups (p > 0.05). The intervention group demonstrated significantly lower post-intervention anxiety scores compared to the control group (34.5 ± 6.8 vs. 42.3 ± 7.2; mean difference = −7.8; p < 0.001). Multivariate analysis confirmed that structured preoperative education was independently associated with reduced anxiety (β = −7.12; 95% CI: −9.85 to −4.39; p < 0.001). Conclusion: Structured preoperative education is an effective and clinically meaningful intervention for reducing anxiety among surgical patients. Integrating standardized educational protocols into perioperative care may enhance patient-centered outcomes and improve surgical service quality in resource-constrained settings.